Optimizing The Role Of Majelis Taklim In Enhancing Family Education During Ramadan - Bahrul Ulum; Usrini, Laisa; Sinuraya, Lidia Anata; Bintang, Nella; Safitra Tanjung , Ramadhani; Samsia Harahap, Nur; Safitri, Rahma (As-sunnah: Jurnal Pengabdian Masyarakat, 2025)
Majelis Taklim strategically enhances family education, especially during Ramadan, through religious activities that support daily Islamic learning. This community service program was conducted in Lingkungan II, Jalan Murai Ujung, Kelurahan Aek Manis, from March 3-17, 2025, using a participatory action research approach based on Asset-Based Community Development (ABCD). The program aims to optimize the role of Majelis Taklim in improving religious understanding, Quranic recitation quality, and consistency in family worship practices. The service partner is the local Majelis Taklim with 50 participants selected through purposive sampling. The methods applied included Islamic family studies, Quranic recitation and tahsin sessions, and collective worship practices using the plan-act-observe-reflect cycle. Results showed an 18% increase in family religious understanding, 22% improvement in Quranic recitation quality, and 15% increase in worship consistency. Program success was supported by active community participation, direct guidance in Quran learning, and communal support in applying Islamic values. This program contributes to strengthening sustainable Islamic family education ecosystems in the community.